2007
DOI: 10.1093/hmg/ddm103
|View full text |Cite
|
Sign up to set email alerts
|

p27 Kip1 localization depends on the tumor suppressor protein tuberin

Abstract: p27(Kip1) plays an important role in cell cycle regulation by inhibiting cyclin-CDK complex activity in the nucleus. p27(Kip1) is regulated by its concentration as well as by its subcellular localization. Tuberin, encoded by the tuberous sclerosis tumor suppressor gene TSC2, is a potent negative cell cycle regulator. We show herein, that tuberin induces nuclear p27 localization by inhibiting its 14-3-3-mediated cytoplasmic retention. Tuberin interferes with 14-3-3's counteracting effects on p27-mediated cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 57 publications
4
40
0
1
Order By: Relevance
“…Rheb depletion induced an evident increase of p27 in both cytoplasmic and nuclear fractions. The increase of p27 in both compartments resembles the one resulting from cell cycle arrest on serum removal in NIH3T3 (Tsc2 þ / þ ) cells (Rosner et al, 2007;Short et al, 2008). Similar results were also observed on overexpression of TSC2 or phosphatidylinositol 3 kinase/Akt inhibition (Rosner et al, 2007;Kim et al, 2009).…”
Section: Rheb Activates Ampksupporting
confidence: 73%
See 4 more Smart Citations
“…Rheb depletion induced an evident increase of p27 in both cytoplasmic and nuclear fractions. The increase of p27 in both compartments resembles the one resulting from cell cycle arrest on serum removal in NIH3T3 (Tsc2 þ / þ ) cells (Rosner et al, 2007;Short et al, 2008). Similar results were also observed on overexpression of TSC2 or phosphatidylinositol 3 kinase/Akt inhibition (Rosner et al, 2007;Kim et al, 2009).…”
Section: Rheb Activates Ampksupporting
confidence: 73%
“…The increase of p27 in both compartments resembles the one resulting from cell cycle arrest on serum removal in NIH3T3 (Tsc2 þ / þ ) cells (Rosner et al, 2007;Short et al, 2008). Similar results were also observed on overexpression of TSC2 or phosphatidylinositol 3 kinase/Akt inhibition (Rosner et al, 2007;Kim et al, 2009). Consistent with the lack of regulation of AMPK activity by mTORC1, we observed that treatment with rapamycin for 2 and 8 h did not alter the nuclear levels of p27 in Tsc2À/À MEFs (Figures 3d and e).…”
Section: Rheb Activates Ampkmentioning
confidence: 80%
See 3 more Smart Citations